PELAPISAN PERMUKAAN BAJA TAHAN KARAT AISI 304 DENGAN KHROM OKSIDA MENGGUNAKAN METODA SPUTTERING - Sungkono; Setiawan, Jan; Isfandi; Aziz, Ikhwanul (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
Stainless steel has been used as structure material of power reactors of LWR, AGR and LMFBR types. The problem of structural materials that arises is low corrosion resistance and swelling in high irradiation environments. One method to overcome this problem is surface coating of the stainless steel cladding with chromium oxide. The aim of this study is to obtain the characteristics of microstructure, microhardness, and compounds formed in the surface layer of AISI 304 stainless steel. DC-sputtering method was used for the coating of AISI 304 surface. The coating process used coater material of chromium target and argon as sputtering gas which was mixed with oxygen gas with concentrations varying from 0 - 50% volume. The process was carried out at 10 - 20 mA current for 1 - 3 hours. Characterization of the layer includes microstructure observation using optical microscope, hardness with microhardness Vickers tester, and compounds analysis in layers with X-ray diffractometer. The results shows that the base metal microstructure is composed of austenite and carbide deposits. The metal-layer interface is clearly visible. The thickness of the resulted compact and homogeneous layer tends to increase for O2 gas composition in the range of 0 – 30 %volume but decrease for the range of 30 - 40 %volume and rise at 40 - 50 %volume. The hardness of the layer increases until oxygen gas is at 30 %volume and then decreases at 50 %volume of O2 gas. At a fixed value of O2 composition at a current of 10 - 20 mA and a process time of 1 - 3 hours, it is observed that the hardness of the SS 304 surface layer increases with increasing current and sputtering time. At a composition of 30 %volume of O2, 10 mA current and 2 hours process, the resulted layer contains CrO2.